Positive Impact of using Interactive Whiteboards in Education - Rafieva Bunafsha Rustamovna (Researchparks Publishing, 2021)
Interactive technologies are able to change the nature of education and the principle of material supply today. For an available statement of new information by means of a modern method, the teacher should study innovative opportunities initially carefully. Use of interactive technologies is capable to make the following positive changes to educational process: work of teachers becomes creative and fascinating; learning efficiency of students increases; rise in labor productivity. Understanding the requirements of modern approach to teaching, teachers constantly increase the skill level, seek to seize new techniques and computer technologies, improve skills, participate in competitions in pedagogical skill, create methodical developments. This progress affects improvement of interaction of the user with a program system of interactive dialogue.